Pengaruh Gaya Kepemimpinan Lintas Budaya dan Reward Terhadap Kepuasan Kerja Melalui Beban Kerja: Studi Kasus PT X - Putri Rahma Dhani; Bayu Kurniawan; Ika Indriasari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to examine the influence of cross-cultural leadership style and reward provision on employee job satisfaction, with workload serving as an intervening variable. The research was conducted at PT X, a multinational company managed by foreign leaders who come from diverse cultural backgrounds. As organizations become increasingly global, understanding how leadership and reward systems function in multicultural environments is essential to improving workforce performance and satisfaction. This research applies a quantitative approach using survey methods, with data collected through questionnaires distributed to 105 employees across various departments. The analysis was carried out using structural equation modeling (SEM) to explore both direct and indirect relationships among the variables. The findings show that cross-cultural leadership style has a significant positive impact on workload, suggesting that cultural differences in leadership influence how employees perceive and handle their tasks. Furthermore, reward provision shows a strong and direct influence on job satisfaction, highlighting the importance of fair compensation and recognition in motivating employees.Importantly, the study also finds that workload partially mediates the relationship between leadership style and job satisfaction. This indicates that leadership practices affect job satisfaction not only directly but also through the perceived amount and nature of the work assigned. These results underscore the necessity for companies, particularly those with a multicultural workforce, to adopt inclusive leadership models and implement transparent, performance-based reward systems. By doing so, organizations can create a more supportive work environment, improve employee morale, and ultimately enhance overall productivity and satisfaction.